PENERAPAN TEORI DIFUSI INOVASI PADA PEMBELAJARAN ORANG PENGARUH KARAKTERISTIK PETANI, PENGUATAN KAPASITAS KELOMPOK TANI DALAM USAHA PELAYANAN JASA ALAT MESIN PERTANIAN (UPJA) DI WILAYAH BPP PLAYEN GUNUNG KIDUL - Sukadi, Sukadi (Jurnal Ilmu-Ilmu Pertanian, 2019)
This study aims to determine the influence of farmers characteristics, strengthening individual capacity, strengthening institutional capacity, strengthening network capacity for agricultural machine tool services (UPJA). Research in the district Playen, Kabupaten Gunung Kidul, research conducted in July to December 2018, the type of quantitative research, type of primary data, sampling technique using purposive sampling, questionnaire data collection techniques, the results of the study showed that: 1) Age of respondents between 40-55 years is 46.7 %; 2) Education of respondents mostly high school is 53.3%; 3) Less than 1-year UPJA experience is 70% of respondents. The results of the regression analysis that have an effect on age affect the (UPJA) value of Sig. 0.046 at the level of 5% and network capacity affects the (UPJA) value of Sig. 0.083 at the level of 10%.